Influence of technological heredity on reliability parameters of products - Кузін, Олег Анатолійович; Кусий, Ярослав Маркіянович; Топільницький, Володимир Григорович (Technology audit and production reserves, 2015)
It is grounded an expediency of systematic approach to solution the problem of product reliability with implementation of comprehensive system of product (machine) lifecycle management (Product Lifecycle Management – PLM), designing the functionally-oriented technologies of engineering production by parallel engineering means – CAPE (Concurrent Art-to-Product Environment). The role of technological inheritance in the technological chain of manufacturing products is determined. It is shown the importance of blanking operations in study of impact of technological inheritance on quality parameters of the final product due to the close relationship of structural and technological inheritance. It is developed the mathematical relationship, which determines the reliability of technological process P(t) implementation given the current state of science and technology. It is shown the priority of finishing and strengthening operations based on surface plastic deformation over the finish machining operations to ensure the desired performance and reliability. In particular, treatment by vibration-centered strengthening of drilling pump cylinder sleeves helped reduce the high-level and step parameters of the surface layer (Ra, Rz, Rp, Rmax) in 1,5-5,8 times and increase the mean time between failures to 1,79 times compared with the original polished and treated bushings. The ways for further research towards optimizing the structure of processes are marked taking into account technological inheritance; practical recommendations on the use of energy-saving technologies, including the use of vibration to improve the performance of machine parts.